Molecular Characterization of Pasteurella multocida: Its Implication with Epidemiology and The Development of Local Isolate Vaccines - ., Supar; Ariyanti, Tati (Indonesian Bulletin of Animal and Veterinary Sciences, 2007)
Pasteurella multocida strains are the causative agents of pasteurellosis attacking Â wide range domestic and wild animals. The important pasteurellosis in animals in Indonesia are Haemorrhagic septicaemic (HS) or Septicaemia epizootica (SE) in large and small ruminants, fowl cholera in poultry and water powls. HS associated with P. multocida in large ruminants was controlled by killed whole cell vaccines produced by the use of P. multocida Katha strain, whereas fowl cholera was controlled by antimicrobial drugs. At present, there are only a limited molecular biology techniques have been applied to investigate P. multocida isolates from different geographic locations in Indonesia. Genomic DNA of P. multocida from HS cases from various provinces which were treated with restriction endonuclease ApaI and analysed by means of pulsed-field gel electrophoreses (PFGE) demonstrated the presence of high degree distinctive DNA pattern compared to that of the vaccine (Katha) strain from Burma and other reference strains. Similar different patterns were found in genomic DNA of local P. multocida isolates from cholera disease of chicken and ducks. P. multocida isolates from some provinces showed different DNA patterns to each other. These DNA pattern differences were probably associated with the alteration of their pathogenicity, antigenicity and immunogenicity, but it has not been confirmed yet. Vaccines prepared from P. multocida isolate originated from local HS cases and local cholera demonstrated better protection in experimental animals against heterologous and homologous challenges, in terms of higher and consistency antibody responses compared to that of Katha strain or imported P. multocida poultry strains. This supports the potential aspects of molecular characterization of local P. multocida isolates kept at the BCC Unit. These isolates may play an important role in developing local master seeds to produce pasteurellosis local vaccines which would be more promising to be used in Indonesia in the future but further field trials are still needed. Â  Key words: Pasteurella multocida, characterization, DNA analysis, vaccines